(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1991)
Detailed stratigraphic work in the course of four geologic expeditions has allowed refinement of the Early Cretaceous stratigraphy of the Zanskar Range. The Giumal Sandstone, which is comprised between the Late Jurassic to earliest Cretaceous? Spiti Shale and the mid-Cretaceous Chikkim and Fatu La pelagic limestones, is formally elevated to Group rank and subdivided into two new formations, both capped by laterally continuous condensed sections here considered as formal stratigraphic horizons. The Takh Formation, overlying the Spiti Shale stratigraphically in the Zumlung Unit and commonly with tectonic contact in the Zangla Unit, is in turn subdivided into two parts. The lower part (62 to 86 m thick in the Zumlung Unit) is characterized by very fine to fine-grained subarkoses and medium to very coarse-grained quartzarenites derived from the rejuvenated Indian continental block. In the upper part (103 to 117 m thick), deeper-water dark pelites locally yielding ill-preserved faunas probably Aptian in age become more important. The formation is capped by a glauconitic marker horizon (Labar La Arenite), testifying to a major starved transgressive stage possibly close to the Aptian/Albian boundary. The Pingdon La Formation (214 to 240 m thick in the southwestern part of the Zangla Unit and only 92 to 130 m thick in the Nerak area and Zumlung Unit) is characterized by the sudden appearance of up to medium-grained volcanic detritus. Decametric intervals of up to very coarse-grained quartzo-feldspathic sandstones characterize the middle part of the formation in proximal areas, whereas more monotonous distal sections contain only up to lower fine-grained volcanic arenites. In the upper part, volcanic arenite layers are interbedded with glaucony-rich or bioclastic sediments yielding sporadic foraminifers of Late Albian age. The formation is capped by a condensed horizon (Nerak Glauco-phosphorite) of Late Albian age (R. subticinensis Subzone), which in distal areas is overlain by latest Albian multicolored pelagic limestones of the Fatu La Formation. In the western part of the Zangla Unit, another condensed horizon rich in phosphates, glaucony and bioclasts (Oma Chu Glauco-phosphorite), reaching up to the Late Cenomanian (W. archaeocretacea Zone), is followed by Early Turonian grey pelagic limestones of the Chikkim Formation. Final drowning of the Zanskar shelf occurred through successive episodes of starvation and deepening, related to a complex interplay of geodynamic, eustatic and paleoceanographic processes.